Trace Elements Content of Mangium Pulp throughout ECF Bleaching Stages as Measured by ICP - Nyoman Wistara; Devi Nurmala (Masyarakat Peneliti Kayu Indonesia, 2015)
The fate of metals in pulp of the five years old mangium wood (Acacia mangium Wild) during bleaching process was investigated. The wood was divided into tree division, i.e. bottom, middle and upper divisions. The wood was chipped and kraft pulped to achieve a kappa number of 14 + 0.5. The resulting pulps were then bleached following an elementally chlorine free (ECF) method of D0, EO, D1, D2 and P sequences. The measurement of metals content was carried out with Inductively Coupled Plasma (ICP) type Optical Emission Spectrometry (OES) Optima 4300DV. Brightness and viscosity of bleached pulps were measured in accordance with TAPPI T 525 om - 92 and TAPPI T 230 om-89 standard procedures, respectively. It was found that, metals content of five years old Acacia mangium tended to increase from the bottom to the upper divisions of the stem. Beyond the EO stage, the content of Mn reduced to below detrimental limit required in peroxide bleaching, which is of 1 ppm. However, the content of Cu and Fe of pulp from every stage of bleaching sequences were much higher than their detrimental limit, i.e. 0.5 ppm and 2 ppm, respectively. Metals content were also found to reduce brightness gain in ECF bleaching.Keywords: Acacia mangium, brightness, ECF bleaching, metals, viscosity